Pengaruh perlakuan alkali NaOH terhadap kekuatan tarik dan fatik kayu merbau - Harnowo Supriadi; Aldy Iwang Ramadhan; Mohammad Badaruddin (TURBO [Tulisan Riset Berbasis Online], 2022)
Merbau wood is a type of tropical hardwood class I-II having resistance to humid weather and so that the wood is widely used in many building constructions, such as bearing houses and bridges. In addition, this wood can be used as a raw material for furniture because it has a high durability and resistance against fungi. The tensile test specimen (ASTM D4761) and the fatigue test specimen (ASTM E466) were made by turning and smoothing the surface with sandpaper. Furthermore, alkaline treatment using various concentrations of NaOH solution (5%, 10% and 15%) was applied to merbau wood by immersing all specimens for 2 h and continued with the drying process at 60 Â°C for 5 h. Tensile and fatigue tests were axially carried out using MTS Landmark 100 kN. The results of the tensile test showed that the tensile strength of merbau wood with 5%NaOH alkali treatment was higher (smax = 202.8 MPa) compared to merbau wood soaked in a solution of 10%NaOH (sult = 149.7 MPa) and 15%NaOH (sult = 129.9 MPa). Likewise, the fatigue life of merbau wood soaked in a 5%NaOH solution is longer than that of merbau wood soaked in a 10% and 15%NaOH solution.